2007
DOI: 10.1016/j.jtcvs.2007.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Aprotinin is safe in pediatric patients undergoing cardiac surgery

Abstract: In this retrospective cohort study of pediatric patients undergoing cardiopulmonary bypass, there was no association between the use of aprotinin and acute kidney failure, need for dialysis, neurologic complications, and operative or late mortality. We continue to use aprotinin for all pediatric patients undergoing cardiopulmonary bypass.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
41
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(45 citation statements)
references
References 23 publications
(21 reference statements)
4
41
0
Order By: Relevance
“…Aprotinin, a basic polypeptide and non-specific proteinase inhibitor, can inhibit several proteases with serine active groups. Recently, aprotinin became no longer restricted to the treatment of patients with acute pancreatitis; it is being used more and more in cardiac surgeries, orthopedic surgeries and liver transplantations [25,26] , and is considered the ideal blood protecting drug.…”
Section: Discussionmentioning
confidence: 99%
“…Aprotinin, a basic polypeptide and non-specific proteinase inhibitor, can inhibit several proteases with serine active groups. Recently, aprotinin became no longer restricted to the treatment of patients with acute pancreatitis; it is being used more and more in cardiac surgeries, orthopedic surgeries and liver transplantations [25,26] , and is considered the ideal blood protecting drug.…”
Section: Discussionmentioning
confidence: 99%
“…Although off-label use of aprotinin was common among congenital heart surgeons, high-quality studies were lacking. [466][467][468] The FDA has never approved a specific pediatric indication for aprotinin, and with the 2007 restrictions, it is no longer available for pediatric cardiac surgery in the United States.…”
Section: Prevention and Treatment Of Postoperative Coagulopathymentioning
confidence: 99%
“…aprotinin, although in children it has been not reported significant adverse effects as noted in adults [11][12][13], and associated with the fact that there is little information available about its influence on the systemic inflammatory response at hemostatic doses, these considerations have led to this study, which aimed to show hemostatic benefit with the use of aprotinin in high doses in acyanotic cardiopathic children operated with CPB by assessing the possible anti-inflammatory effect associated, which was not confirmed in this series.…”
Section: Fig 6 -Il-6/il10 Proportion In the Aprotinin And Control Grmentioning
confidence: 71%
“…However, in recent retrospective cohort studies of children who had undergone surgery with CPB, there was no association between use of aprotinin and renal failure, dialysis, neurologic complications and mortality [11], and reported that the CPB time over 100 minutes was the main marker of postoperative renal dysfunction in neonates but not the use of the drug, which was not associated with this risk in the immediate postoperative period [12,13]. The use of safety data in adults for pediatric practice requires caution and is of questionable validity, since they are two distinct populations with distinct risk factors, and drugs that have the greatest risk of complications in adults can be safe in children, and vice versa.…”
Section: Introductionmentioning
confidence: 98%